Pengaruh Motivasi Belajar dan Persepsi Kemampuan Berpikir Kritis Terhadap Hasil Belajar - Selsa Della Fitri; Armida S (Jurnal Ecogen, 2020)
This study aims to determine how the influence of learning motivation and the perception of critical thinking skills on economic learning outcomes in class X IPS SMA Adabiah 2 Padang. This type of research is a causal descriptive and associative research using SPSS version 26. The instruments used in this study were questionnaires and research documentation. The existing population of 102 students in sampling using proportional random sampling with a total of 82 students. The instrument trials used validity and reliability tests. Data analysis with descriptive and inductive analysis using the normality test, heterokedasticity test, multicollinearity test, multiple regression test and hypothesis test using the F test and t test. From the results of the study show: (1) Learning Motivation and Perception of Critical Thinking Ability together have a positive and significant influence on student economic learning outcomes seen from the value of sig. 0,000> 0.05. (2) There is a positive and significant influence of learning motivation on student economic learning outcomes seen from Sig. 0,000> 0.05. (3) There is no significant effect on the perception of critical thinking skills on economic learning outcomes seen from Sig. 0.946> 0.05. Keywords: learning motivation, perception of critical thinking ability, learning outcomes